MATERIALISM OF THE MODERN CIVILIZATION AND ECOLOGICAL ETHICS (Annual of the Faculty of Philosophy in Skopje, 2014)
In the paper it is discussed about subjects that are in immediate relation to the ecological ethics. More precisely, on the beginning the analysis is guided towards some definitional concepts related to ethics, traditions and morality. After that, the author is focused on the ecological questions in the m odern civilization, with special accent on the anthropocentrically and bio - centrically view of the world, f or the environment and in the field of the ethical influence of the human. In the analysis are exposed some theoretical views that analyze the relation of the human towards the nature and other living beings and the possibilities for forming one ecological ethics or bio - ethics. At the end, in the conclusion, the author sets the basic dilemma for the possibility offorming an ecological ethics, for relativism, for abandoning the narrow view on the world, that is typical for classical economy and anthropocentric and for the pluralism in the ethical discussions for the relation of the human and outside world.
Keywords: MORALE; ETHICS; ECOLOGICAL ETHICS; BIOETHICS; ANTHROPOCENTRISM; BIOCENTRISM